2005
DOI: 10.1002/anie.200462946
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Mediated Selective Oxidation of a CH Bond

Abstract: An environmentally friendly procedure has been developed for the oxidation of 2,4,6‐trimethylphenol (TMP) at the para C sp 3–H bond. Upon reaction with H2O2 in the presence of catalytic amounts of CuII and neocuproine in methanol at 65 °C, 4‐(methoxymethyl)‐2,6‐dimethylphenol (MDP) or 4‐hydroxy‐3,5‐dimethylbenzaldehyde (HDB) is formed (see reaction).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…[49] Complexes 1-3 and 5: The two consecutive irreversible oxidation peaks observed with the Zn-pyramol complexes 2 and 3 (Table 2 and Figures 16 and 17) are assigned to the ligand dehydrogenation (pyramol to pyrimol), and to the phenoxyl radical formation and its consequent oxidation products, respectively (as observed for the free ligand Hpyramol). Similarly, the sole irreversible oxidation peak observed in the voltammograms of the Zn-pyrimol complexes 1 and 5 corresponds to the oxidation of the phenolic moiety to phenoxyl radicals, and the subsequent oxidation products.…”
Section: Full Papermentioning
confidence: 90%
“…[49] Complexes 1-3 and 5: The two consecutive irreversible oxidation peaks observed with the Zn-pyramol complexes 2 and 3 (Table 2 and Figures 16 and 17) are assigned to the ligand dehydrogenation (pyramol to pyrimol), and to the phenoxyl radical formation and its consequent oxidation products, respectively (as observed for the free ligand Hpyramol). Similarly, the sole irreversible oxidation peak observed in the voltammograms of the Zn-pyrimol complexes 1 and 5 corresponds to the oxidation of the phenolic moiety to phenoxyl radicals, and the subsequent oxidation products.…”
Section: Full Papermentioning
confidence: 90%
“…To ascertain the influencing factors, NaOMe was added to test the influence of the basic cocatalyst on the reaction because NaOMe is believed to have the power to remove protons from the phenol substrate and thus facilitate the oxidation of the phenol in homogeneous systems 14. Furthermore, Reedijk et al have reported that the NaOMe and phenol can bridge two copper atoms to form a mixed μ‐methoxido‐μ‐phenoxido‐bridged dinuclear copper species, namely neocuproine which is the key intermediate of the reaction 13a. As shown in Table 1, when NaOMe was added as the cocatalyst, the PPE selectivity decreases for both 1 and 2 and the conversion of DMP for 1 decreases.…”
Section: Resultsmentioning
confidence: 99%
“…Next, a survey of the activity of other copper salts revealed Cu(OAc) 2 to be the most effective catalyst for the esterification (Table 1, entries [5][6][7][8][9][10][11][12][13][14]. Copper(II) halides like CuCl 2 and CuBr 2 only provided trace amounts of the esterified product (Table 1, entries 5 and 6).…”
Section: Letter Syn Lettmentioning
confidence: 99%